rewrite the expression in terms of the first power of cosine

sin^4x

so far i have

(sin^2x)^2

= (1-cos2x/2)^2

= (1-cos2x/2)(1-cos2x/2)

=1-cos^2.2x/4

so my question is, is it right? or is there more

Printable View

- May 16th 2010, 08:42 PMreino17lowering powers
rewrite the expression in terms of the first power of cosine

sin^4x

so far i have

(sin^2x)^2

= (1-cos2x/2)^2

= (1-cos2x/2)(1-cos2x/2)

=1-cos^2.2x/4

so my question is, is it right? or is there more - May 16th 2010, 09:32 PMSoroban
Hello, reino17!

Your algebra is off . . .

Quote:

Rewrite the expression in terms of the first power of cosine: .

.

Multiply by

- May 16th 2010, 10:03 PMreino17
ahh ok i see where i screwed up. thanks dude